Atividades antibiofilme e fungicida de 2-bromo-n-fenilacetamida frente a Candida spp. fluconazol-resistentes - Teixeira, Bráulio de Almeida (2024)
Microorganisms of the Candida genus are responsible for numerous clinical conditions, ranging from localized mycoses such as onychomycosis, oral candidiasis and vulvovaginal candidiasis to systemic mycoses like disseminated candidiasis. Candida spp. are among the primary agents causing death attributed to fungal infections with notable emphasis on species such as Candida albicans, Candida tropicalis, Nakaseomyces glabratus (Candida glabrata) and Candida parapsilosis. These microorganisms are also renowned for their remarkable resistance to antifungal drugs through various mechanisms, including alternative metabolic pathways, biofilm formation, mutations in genes for ergosterol synthesis and overexpression of efflux pumps. The search for new synthetic antifungal molecules represents a therapeutic alternative in this scenario, given the potential for discovering new pharmacological classes or new combined therapy schemes with classical antifungals. In this study, the antifungal profile of a synthetic amide, 2-bromo-N-phenylacetamide, was investigated against C. albicans, C. tropicalis, N. glabratus (C. glabrata) and C. parapsilosis through different assays. 2-bromo-N-phenylacetamide ("A1Br") exhibited fungicidal activity with a Minimum Inhibitory Concentration (MIC) of 32 μg.mL-1 for 87.5% of the tested strains and a Minimum Fungicidal Concentration (MFC) of 64 μg.mL-1 for 81.25% of the microorganisms. It also proved to be a potent agent against mature biofilms of C. albicans with a reduction ranging from 59-80%, statistically as significant as that of amphotericin B (reduction of 32-83%) when comparing each of these treatments to the control group. When combined with the licensed antifungals fluconazole and amphotericin B the molecule "A1Br" exhibited indifferent effects. Its mechanism of action remains to be elucidated since no changes were observed in its MIC in sorbitol and ergosterol assays.